Muscle Injuries in Sport Medicine - Nicola Bisciotti, Gian; Eirale, Cristiano (IntechOpen, 2013)
Muscle tears are one of the most common pathologies in sport and one of the most frequent causes of sport activity suspension. The purpose of this book is to review the state of the art of the actual knowledge on muscle tears in athletes, in particular for what concern the biology of muscle healing, the conservative and surgical treatments and the preventive aspects. Therefore, this textbook can be a valid tool for all Sport Medicine practitioners such as physicians, physiotherapists and fitness coaches.